P-650 Partial premature ovulation detection during follicular aspiration compromises the quantity but not the quality of the retrieved oocytes in stimulated fresh IVF cycles. (30th June 2022) - Rodríguez Varela, C; Gómez, V.H; Bosch, E; Labarta, E
Abstract: Study question: Is partial premature ovulation (PPO) detection during the oocyte pick-up (OPU) a sign of poor prognosis in in vitro fertilization (IVF) cycles with own oocytes? Summary answer: PPO halves the number of metaphase II oocytes available for an IVF treatment without reducing their quality, demonstrated by unaltered fertilization and top-quality blastocyst rates. What is known already: PPO detected during the OPU procedure has not been extensively studied in the literature. This phenomenon may result in a reduction in the number and/or competence of the oocytes retrieved, due to the potential loss of the already expelled oocytes, as well as the likely dominance exerted by the ruptured follicle/s in the rest of the cohort. Despite this, several authors have demonstrated that competent oocytes can be retrieved from these already ruptured follicles, suggesting that oocyte extrusion frequently does not occur after follicle rupture. The potential negative effect exerted in the rest of sibling oocytes remains unknown. Study design, size, duration: Retrospective cohort analysis performed in IVIRMA Valencia (Spain), including 8994 cycles of controlled ovarian stimulation (COS) for an IVF treatment with fresh own oocytes, between January 2016 and May 2021. OPU procedures for oocyte cryopreservation, as well as mixed cycles with both fresh and frozen oocytes, were discarded. PPO diagnosis was based on ultrasound visualization of any already formed corpus luteum structure/s, a lower follicular count than expected, and/or free fluid. Participants/materials, setting, methods: Female patients undergoing OPU after COS for a fresh IVF treatment. Cycles in which PPO has been detected will be compared with a random, and of the same size, sample without PPO. Mean number of oocytes, metaphase II, fertilized oocytes and top-quality embryos, as well as IVF success rates, will be compared between both groups. Patients' basal characteristics and COS parameters will be analyzed in order to detect any potential early indicator of PPO. Main results and the role of chance: PPO was detected in 123 of the 8994 cycles (1.37%) performed. A random control group of 123 cycles without PPO was selected. Patients' mean age was 37.6±3.6, with a BMI of 23.3±4.1 kg/m 2 and an anti-mullerian hormone of 1.62±1.3 ng/mL. Patient's basal characteristics and COS parameters were statistically comparable among groups (p > 0.05), except for lower serum estradiol levels (2037.64 vs. 1582.24 pg/mL; p = 0.004) in the PPO group on the last ultrasound prior to OPU. Patients with PPO showed lower aspiration rates (88.95% vs. 55.78% in the PPO gr.), as well as a reduced mean number of oocytes (10.69 vs. 5.68 in the PPO gr.), metaphase II (8.41 vs. 4.33 in the PPO gr.), fertilized oocytes (6.23 vs. 3.26 in the PPO gr.) and top-quality blastocysts (2.77 vs. 1.35 in the PPO gr.) (p = 0.000). In contrast, maturation (80.72% vs. 76.57% in the PPO gr.), fertilization (73.52% vs. 75.18% in the PPO gr.) and top-quality blastocyst rates (44.03% vs. 38.68% in the PPO gr.) were statistically similar between both groups (p > 0.05). Limitations, reasons for caution: The main limitations of the present study are its retrospective design and its small sample size, derived from the low frequency of the PPO phenomenon in our clinic. Larger prospective studies should be proposed in order to accurately define the negative impact of PPO in IVF success rates. Wider implications of the findings: PPO clearly reduces the number of oocytes available for an IVF treatment, although it does not seem to impair the competence of the remaining cohort. Once PPO is detected, cycle cancellation may not be worth the associated loss of money, time and morale, especially given its low prevalence (around 1%). Trial registration number: Not applicable